Dziekani w ustawodawstwie synodalnym diecezji włocławskiej - Gręźlikowski, Janusz (Prawo Kanoniczne, 2009)
The introduce analysis the synodal resolution of the dioceses of Włocławek on space eight centuries on angle dean’s office, its authorization, duty and tasks in diocese, give conviction haw important is this office and necessary to realization religious mission of Church and his spiritual mission. From the beginning formation this office, through its evolution and actual obligatory norms of canon law, this office always write in mission of Church, joint action in realize and many methods activity community of the People of God. Moreover office of deans, definite authorizations and obligations always have on in view help of the diocesan bishop in performance pastoral service in particular Church. The deans as representative of presbytery the Włocławek Church, in light discussion rules of Włocławek synodal legislation, had belong and belong to nearest and most trustworthy collaborators of the diocesan bishop and have very important part in structure of this Church. The synodal legislation of Włocławek made and make with dean assistant of the diocesan bishop, mediator between the diocesan bishop and the diocesan curia, and priest and faithful deanery in specified matter. In the beginning dean introduced synodal legislation and orders of the diocesan bishop in life denary and individual parishes, was guardian of faith, customs and discipline. After the Council of Trent this office took bigger meaning and not limit to function control and inspect work priest in deanery, but also administrative in design assistance of the diocesan bishop in control of the diocese. After the Council of Vatican II to duty of the dean join pastoral duty in deanery. On the person dean and his service in big degree depend realization of mission of the Church. The synodal legislation of Włocławek made for detail designation function and assignment of deans servant designs inspection and administration-pastoral of the Włocławek Church. In they light office and service dean had and has take for this, that under leadership of the dean all priest in deanery commit in priesthood realize priest and pastoral vocation, realize duty result with leadership of parish, take cooperation, with fruit will be animation religious and pastoral life in the particular Church, and also will be realize – peaceably with rules of cannon law – service pastoral, sanctify and teaching of faithful.